Disinformation and calculated care beyond the Global North: comparing refugee discourses in Australia and India - Khorana, Sukhmani; Thapliyal, Nisha (Frontiers in Sociology, 2024)
This article explores what “care” looks like in the specific context of Muslim refugees and asylum seekers within the dominant discourse of humanitarianism. India and Australia are chosen for this comparative analysis because our aim is to emphasise multidimensional anti-Muslim alliances that are now in place in both contexts between the governments and official and unofficial media that influence humanitarian policies and practice. We argue that the “information disorder” that dominates current media ecologies about Muslim refugees in both countries is produced at this nexus of official agents—both state and media institutions—as well as social media content produced by local and global actors that perpetuate anti-Muslim bias. More specifically, this article examines how India has responded to emergencies involving the Rohingya refugees, and Australia’s treatment of post-9/11 Muslim refugees and asylum seekers. We demonstrate that these states and the media they sponsor are linked to the use of disinformation, or deliberately inaccurate information to seed and perpetuate Islamophobic sentiments and thereby practice a form of “calculated care”. The examples in this article highlight the need to build on our understanding of what constitutes humanitarian care towards vulnerable and stateless populations. Furthermore, they call for response strategies that take into cognizance the fact that Islamophobia has been institutionalized in the public sphere in order to promote culturally supremacist discourses of traditional values as well as national security.